Posttransplantation Lymphoproliferative Disorder of the Paranasal Sinuses Mimicking Invasive Fungal Sinusitis: Case Report - Gordon, Andrew R.; Loevner, Laurie A.; Sonners, Adina I.; Bolger, William E.; Wasik, Mariusz A. (American Journal of Neuroradiology, 2002)
Summary: Posttransplantation lymphoproliferative disorder (PTLD) is a challenging complication associated with organ transplantation and is usually fatal if untreated. We describe the case of a transplant recipient who presented with rapidly progressive cranial nerve palsies due to PTLD that originated in the sphenoid sinus. In this case, the clinical and radiologic presentation of PTLD mimicked invasive fungal disease. Because the management of PTLD and the management of invasive fungal infection are vastly different, prompt pathologic diagnosis is required.